Prove that
![\frac{ log_{a}(x) }{ log_{ab}(x) } = 1 + log_{a}(b) \frac{ log_{a}(x) }{ log_{ab}(x) } = 1 + log_{a}(b)](https://tex.z-dn.net/?f=+%5Cfrac%7B+log_%7Ba%7D%28x%29+%7D%7B+log_%7Bab%7D%28x%29+%7D++%3D+1+%2B++log_%7Ba%7D%28b%29+)
for permissible values of letters involved in the result.
Answers
Answered by
2
using below two formulas
![log_{a}(x ) \div log_{ab}(x) = log_{x}(ab) \div log_{x}(a) log_{a}(x ) \div log_{ab}(x) = log_{x}(ab) \div log_{x}(a)](https://tex.z-dn.net/?f=+log_%7Ba%7D%28x+%29++%5Cdiv++log_%7Bab%7D%28x%29++%3D++log_%7Bx%7D%28ab%29++%5Cdiv++log_%7Bx%7D%28a%29+)
we know that
![log_{a}(b) = 1 \div log_{b}(a) log_{a}(b) = 1 \div log_{b}(a)](https://tex.z-dn.net/?f=++log_%7Ba%7D%28b%29++%3D+1+%5Cdiv++log_%7Bb%7D%28a%29+)
and
![log_{a}(b) = log_{x}(b) \div log_{x}(a) log_{a}(b) = log_{x}(b) \div log_{x}(a)](https://tex.z-dn.net/?f=+log_%7Ba%7D%28b%29++%3D+++log_%7Bx%7D%28b%29++%5Cdiv++log_%7Bx%7D%28a%29+)
now (using above formula)
![\frac{ log_{x}(ab) }{ log_{x}(a) } = log_{a}(ab) \frac{ log_{x}(ab) }{ log_{x}(a) } = log_{a}(ab)](https://tex.z-dn.net/?f=+%5Cfrac%7B+log_%7Bx%7D%28ab%29+%7D%7B+log_%7Bx%7D%28a%29+%7D+%3D++log_%7Ba%7D%28ab%29++)
we know
log ab= log a + log b
similarly
![log_{a}(ab ) = log_{a}(a) + log_{a}(b) log_{a}(ab ) = log_{a}(a) + log_{a}(b)](https://tex.z-dn.net/?f=+log_%7Ba%7D%28ab+%29++%3D++log_%7Ba%7D%28a%29++%2B++log_%7Ba%7D%28b%29+)
we know that
![log_{a}(a) = 1 log_{a}(a) = 1](https://tex.z-dn.net/?f=+log_%7Ba%7D%28a%29++%3D+1)
we get
![log_{a}(a) + log_{a}(b) = 1 + log_{a}(b) log_{a}(a) + log_{a}(b) = 1 + log_{a}(b)](https://tex.z-dn.net/?f=+log_%7Ba%7D%28a%29++%2B++log_%7Ba%7D%28b%29++%3D+1+%2B++log_%7Ba%7D%28b%29+)
here we got the final answer
hence proved
we know that
and
now (using above formula)
we know
log ab= log a + log b
similarly
we know that
we get
here we got the final answer
hence proved
SpideyAbhi:
did you like my answer
Similar questions